Effect of 5-fluorouracil chemotherapy and the potential protective effect of the SSRI antidepressant fluoxetine on memory and neurogenesis in the adult hippocampus - EL-Beltagy, Maha (2010)
*Please note: The abstract, acknowledgments, list of publications, table of contents and abbreviations in this PDF file appear in a different order to that of the print version of this thesis.